Hans Chr. Garmann Johnsen, Stina Torjesen & Richard Ennals (eds.), Higher Education in a Sustainable Society. A Case for Mutual Competence Building (Dordrecht: Springer, 2015) - Hermína Gunnþórsdóttir (Nordicum-Mediterraneum, 2017)
A review of the book: Hans Chr. Garmann Johnsen, Stina Torjesen & Richard Ennals (eds.), Higher Education in a Sustainable Society. A Case for Mutual Competence Building. (Dordrecht: Springer, 2015)